Post-occupancy evaluation to improve the clinical laboratory in tertiary hospitals in Shaoxing - Liu, Wenzhao (2019)
Nowadays, medical technology is developing at high speed, and laboratory medicine has been developed. As a hospital clinical laboratory in vital sectors, the laboratory is getting more and more attention from society. It not only needs to meet the work needs of the inspectors, but also considers the psychological needs of the inspectors. An efficient and clean working environment helps improve the efficiency and work comfort of inspectors. In China, most of the laboratory design does not have efficient circulation planning, and there is no clear functional division, which hinders the space of the laboratory from achieving maximum efficiency. Relatively few researchers have investigated the impact of the physical environment on inspectors. This research concentrates on the effect of the design of the clinical laboratory to develop an efficient and clean environment for inspectors. A method combining practice and theory is proposed to investigate the spatial and social attributes of the laboratory. According to the design before and after the reconstruction of the same hospital's laboratory, the spatial layout of the laboratory is analyzed and studied to understand the work requirements and work of the inspectors. Based on the spatial syntactic theory, the layout of the laboratory is simulated by measuring the spatial properties of the laboratory plan. The comparative analysis of the results reveals the problems that need to be improved in the laboratory, This study also proposes methods for laboratory improvement and behavioral research, which can be used in other studies. In addition to spatial layout design, architects also need to consider other influencing factors, including the location and orientation of the room and users’ psychology. Keywords: Clinical laboratory design, Space Syntax, Spatial design